Simulation of Soil N2O Emissions Under Different Soil Moisture Conditions by Using Mixed Dynamic Equation - Tang Kun; Zheng Yixin; Zhao Chengzheng; Duan Shufang; Gao Mingxia; Feng Hao; Sun Benhua (Shuitu baochi tongbao)
[Objective] Soil moisture has an important impact on N2O emissions. This study attempted to simulate the cumulative process of soil N2O emission under different soil moisture conditions by using a mixed dynamic equation, and to analyze the influence of soil water on N2O production pathway and its variation rule in order to provide theoretical and practical guidance for reducing N2O gas emissions through improving soil management. [Methods] Soil N2O emission characteristics, the dynamics of ammonium and nitrate nitrogen content, and oxygen consumption were studied under different soil moisture conditions 〔40% water-holding capacity (WHC), 60% WHC, 80% WHC, 100% WHC, and flooded〕. [Results] ① The N2O emission rates reached maximum values at 24 h. Emissions from the flooded treatment 〔3.46 μg/(kg·h)〕 were 54.5—178.9 times greater than from the other treatments. ② The cumulative emission of soil N2O increased with increasing incubation time, and the rapid rise stage occurred in the first 48 h for the flooded treatment. The rapid rise stage occurred in the first 96 h for other treatments. The cumulative N2O emissions for soil under the flooded treatment (44.6 μg/kg) were 67.1, 29.2, 20.8, and 10.4 times greater than under 40% WHC, 60% WHC, 80% WHC and 100% WHC, respectively, at the end of incubation. ③ Except for the coefficient of determination (R2) of 0.878 for the pseudo-second-order dynamic equation under the flooded treatment, all coefficients of determination were greater than 0.920 for all dynamic equations under all soil moisture treatments. The denitrification process accounted for 9.3%~13.2% of the N2O emissions, and the nitrification process accounted for 86.8%~90.7% of the N2O emissions at the initial 24 h of incubation. At the end of incubation (480 h), the denitrification process accounted for 37.8%~47.5% of the N2O emissions, and the nitrification process accounted for 52.5%~62.2% of the N2O emissions. [Conclusion] The higher the soil moisture content, the greater the emission of N2O, and an emission rate pulse appeared at 24 h. N2O was mainly generated by denitrification under flooded conditions. N2O was mainly generated by nitrification under the 40%~100% WHC conditions. The mixed dynamic equation was able to well simulate the cumulative emission process of soil N2O during the incubation experiment, and can be used to distinguish the amount and proportion of N2O emissions occurring by denitrification and nitrification processes. These results provide a new idea and method for studying the pathways of soil N2O production and emission. The results need to be further verified by field experiments and isotope tracing methods etc.